Irrigation and Nitrogen Management for Optimizing Resource Use Efficiency in Summer Fodder Sorghum under Coastal Tract of South Gujarat - Thakur, M. R.; Patel, J. P. (International Journal of Bio-resource and Stress Management, 2025)
A field experiment was conducted during summer season (March to May) of 2021 at the College Farm, N. M. College of Agriculture, Navsari Agricultural University, Navsari, Gujarat, India, to optimize irrigation schedule, nitrogen dose and schedule of nitrogen application for summer fodder sorghum. Irrigation schedules consisted of irrigation at 0.4, 0.6 and 0.8 IW/CPE. Nitrogen levels were 60 and 80 kg N ha-1 in two equal splits at basal and 30 days after sowing (DAS) and three equal splits at basal, 30 and 45 DAS. Irrigation at 0.8 IW/CPE endorsed the vegetative growth by upholding leaf water retention and thus improved fodder quality, yield, water use efficiency (WUE), partial factor productivity of fertilizer N (PFPFN) and nutrients uptake. Application of 80 kg N ha-1 had significantly increased quality and yield of fodder, WUE and nutrient uptake by promoting vegetative growth. Despite non-monetary input, three splits of N with concurrent improvement in quality parameters recorded 30.4, 28.7, 30.3 and 36.8% higher green fodder yield, WUE, PFPFN and N uptake efficiency (N Upt E), respectively than two splits of N. Synergistic effect of treatments showed that, irrigation at 0.6 IW/CPE with 80 kg N ha-1 in three splits was most lucrative based on benefit-cost ratio. It was also effectual to achieve higher WUE and obtained equivalent fodder yield, PFPFN, N Upt E as that of higher yielded combination i.e. irrigation at 0.8 IW/CPE and 80 kg N ha-1 in three splits with saving of 22.2% (1000 m3) irrigation water.